Design and Development of an Arabic Language Online Learning Module Based on the ADDIE Instructional Design Model - Mohammad Taufiq Abdul Ghani; Nazri Atoh; Zarima Mohd Zakaria; Taj Rijal Muhammad Romli; Saipolbarin Ramli; Elsayed Makki Elbishr Ali Hassan (Ijaz Arabi Journal of Arabic Learning, 2026)
Arabic language education is increasingly transitioning into digital spaces to meet the demands of modern learners and expand accessibility. However, many existing online Arabic learning modules lack structured instructional design, resulting in limited learner engagement and effectiveness. This paper addresses this gap by proposing a systematic approach for developing an Arabic-language online learning module using the ADDIE instructional design model, which comprises five phases: Analysis, Design, Development, Implementation, and Evaluation. The study presents a conceptual application of each ADDIE phase tailored to Arabic language instruction, incorporating needs analysis, learning objectives, content creation, digital tools, and formative assessments. The proposed design framework is expected to result in a more coherent, interactive, and learner-centered module that improves student outcomes in language acquisition. This research contributes to Arabic language pedagogy by offering a replicable model for educators and designers to develop high-quality digital learning materials aligned with pedagogical and technological best practices.